Do medical students want to learn about global health? - Anya Göpfert; Hussein Mohamedbhai; Josko Mise; Anne Driessen; Ambreen Shakil; Ann Fitzmaurice; Wendy Graham (Taylor & Francis Group, 2014)
Background: One objective of the United Nations Global Strategy for Women's and Children's Health relates to ensuring a sufficiently skilled workforce. To prepare future healthcare professionals for their role in the 21st century as members of this workforce, awareness of global health is essential, but few studies have explored student perspectives on such education. The main objectives of this study were to establish the views of medical students on learning about women's and children's health in low-income countries, to identify the nature and extent of learning already experienced, and to assess the demand for such learning. Design: A questionnaire survey was conducted at three meetings of the International Federation of Medical Students Associations (IFMSA). Questionnaires were distributed to 500 participants from 75 countries and 336 medical schools, and 492 usable questionnaires were returned. Data were analysed using SPSS Version 20 and statistical analysis was undertaken using Fisher's exact test. Results: There were 492 questionnaires included in the analysis. Forty-eight per cent of participants were from low-middle income countries and 52% were from high-income countries. Less than half (43%) of the respondents had received some teaching on women's and children's health in low-income countries. Teaching received was primarily (96%) through lectures in the second year of study. Ninety-one per cent of respondents thought such teaching would be important and stated that group work (66%) would be the preferred method. In total, only 14% thought they had received sufficient teaching on global health and on women's and children's health in low-income countries. Conclusions: This study has revealed a high demand among medical students for global health teaching, particularly on women's and children's health in low-income countries. The timing and methods of existing teaching on these topics does not match that desired by medical students. To help address this gap, a collaborative approach is proposed which includes students' views in the processes for revitalising medical curricula to meet the needs of the 21st century.